105 Inside knowledge is power: utilising existing population knowledge to design a contextually appropriate intervention to address sub-optimal feeding practices in a british minority population. (December 2018) - Martin, J; Benton, L; Fottrell, E; Black, G; Lakhanpaul, M
Abstract : Introduction: Adapting interventions developed in low-income countries (LICs) to the UK could offer an alternative to current NHS services. The women's' group, Participatory Learning and Action Cycle (PLAC), has successfully reduced neonatal mortality in LICs. It guides participants through a process involving problem identification, planning strategies and post-implementation evaluation. Child health can be influenced by the health of the mother and affected also by factors such as infant nutrition. Sub-optimal nutrition in infancy could be creating high rates of nutrition-related ill-health in British Bangladeshis. Tower Hamlets boasts a large and concentrated population of British Bangladeshis, which presents a receptive environment for participatory programmes. The aim of this project is to utilise existing population knowledge, to adapt the PLAC to encourage optimal infant feeding practices in the Bangladeshi population of Tower Hamlets. Aims: Using Braun and Clarke (2006) guidelines, we thematically analysed three focus group discussions with men and women of Bangladeshi origin, in Tower Hamlets. Results: The participants perceived British Bangladeshi practices to be distinct from those living in Bangladesh, particularly regarding family dynamics, health professional influence and health priorities. This indicates that the PLAC needs to be available to all family members, be embedded in the NHS and focus on child growth and development. The content of the intervention will include resources such as picture cards, which will include traditional Bangladeshi foods as well as British recipes. Conclusions: British Bangladeshi communities identify in terms of their heritage and their environment. This has implications for interventions such as the PLAC that are being adapted from LICs. Minority groups living in the UK may be accustomed to British culture, particularly where food and family ties are concerned. Utilising existing population knowledge is an effective way to adapt for assimilation or acculturation in such populations.